2011
DOI: 10.1161/circheartfailure.110.960450
|View full text |Cite
|
Sign up to set email alerts
|

Fish Intake and the Risk of Incident Heart Failure

Abstract: Background Whether fish or the fatty acids they contain are independently associated with risk for incident heart failure (HF) among postmenopausal women is unclear. Methods and Results The baseline Women’s Health Initiative Observational Study (WHI-OS) cohort consisted of 93,676 women aged 50–79 of diverse ethnicity and background of which 84,493 were eligible for analyses. Intakes of baked/broiled fish, fried fish and omega-3 fatty acid (eicosapentaenoic acid (EPA) + docosahexaenoic acid (DHA), α-linolenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
60
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 27 publications
3
60
1
1
Order By: Relevance
“…However, intake of 18 : 3n-3 was relatively 0·26 0·33 0·26 0·35 0·24 0·36 0·23 0·37 0·26 Soya products (servings/week) 0·1 0·2 0·1 0·3 0·2 0·3 0·3 0·5 0·7 1·7 Nuts (servings/week) 0·2 0·3 0·2 0·4 0·3 0·4 0·4 0·6 0·6 1·5 Mayonnaise (servings/week) 0·2 0·4 0·3 0·4 0·4 0·4 0·5 0·5 0·8 1·7 Salad dressing (servings/week) 0·5 1·0 0·7 1·1 0·8 1·3 1·1 1·5 2·2 2·6 low; an association between 18 : 3n-3 and HF may be evident at higher levels of intake than observed in the Swedish Mammography Cohort. The present results are consistent with a recent large study of women from the USA, which also failed to find an association between 18 : 3n-3 and HF (16) . In addition,…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, intake of 18 : 3n-3 was relatively 0·26 0·33 0·26 0·35 0·24 0·36 0·23 0·37 0·26 Soya products (servings/week) 0·1 0·2 0·1 0·3 0·2 0·3 0·3 0·5 0·7 1·7 Nuts (servings/week) 0·2 0·3 0·2 0·4 0·3 0·4 0·4 0·6 0·6 1·5 Mayonnaise (servings/week) 0·2 0·4 0·3 0·4 0·4 0·4 0·5 0·5 0·8 1·7 Salad dressing (servings/week) 0·5 1·0 0·7 1·1 0·8 1·3 1·1 1·5 2·2 2·6 low; an association between 18 : 3n-3 and HF may be evident at higher levels of intake than observed in the Swedish Mammography Cohort. The present results are consistent with a recent large study of women from the USA, which also failed to find an association between 18 : 3n-3 and HF (16) . In addition,…”
Section: Discussionsupporting
confidence: 93%
“…A higher intake of 18 : 3n-3 has been associated with a lower rate of CHD in some populations (13 -15) , but a recent study did not find an association with HF (16) . Overall, supplementation with neither 18 : 3n-3 nor long-chain n-3 fatty acids significantly reduced major cardiovascular events in a recent trial in people with a history of MI (17) .…”
mentioning
confidence: 99%
“…High consumption of fried foods in general has previously been reported to be associated with type 2 diabetes [42], as well as general and central obesity [43, 44], high blood pressure [44] and development of the metabolic syndrome [45]. In studies observing inverse associations between non-fried fish consumption and risk of heart failure [23, 26], ischaemic heart disease [22], stroke [24] and atrial fibrillation [25], high consumption of fried fish has been associated with higher risk or no association. Absorption of fat during frying results in more energy-dense foods and may contribute to a higher overall fat intake.…”
Section: Discussionmentioning
confidence: 99%
“…Frying of fish could potentially be of importance because of formation of advanced glycation end products (AGEs) [20], mutagenic compounds [21], changes in fatty acid composition or increased energy–density. Further, studies on CVD where fried fish was distinguished from non-fried fish have indicated that the associations may vary by preparation method [2226]. Contaminants present in fish may also be of importance.…”
Section: Introductionmentioning
confidence: 99%
“…While some studies have reported a lower risk of HF with consumption of baked or broiled fish 3234 as well as higher plasma of dietary EPA/DHA 35 , such findings have not been consistent across studies. The observational arm of the Women’s Health Initiative 36 reported a lower risk of HF with fish consumption but no association between dietary EPA/DHA and incident HF. Given the inconsistency in the literature on the role of omega-3 fatty acids and HF risk, it is important to clarify whether marine omega-3 fatty acids confer a lower risk of HF.…”
mentioning
confidence: 97%